Conhecimento e monitoramento metacognitivo em tarefas que envolvem criatividade - Deffendi, Luma Tiziotto (Universidade Federal de São Carlos, 2019)
Metacognition can be understood as the knowledge the individuals have about their own cognitive processes and that allows the monitoring and regulation of their cognitive activities. From the cognitive point of view, creativity is the name given to a group of processes that tend to facilitate the elaboration of new and unprecedented forms of grouping. The aim of this thesis was to approach, in an integrated way, the relationship between the two contours: metacognition and creativity, considering that such interaction isn´t explored in the scientific scene, especially in the national scene. The thesis was organized in three manuscripts in order to facilitate the understanding of the general objective mentioned above. In the first manuscript the aim was to prepare the reader for subsequent studies, and for that scientific productions about metacognitive monitoring and creativity in the last twelve years were analyzed. The second manuscript describes a correlational study, in which metacognitive knowledge and monitoring of university students were investigated during figural and verbal creativity tests. The metacognition was evaluated, in turn, through the application of the techniques developed by the researchers for this purpose, and from the description of the creative characteristics present in the manuals of crativity tests. From the data obtained in the second study, the third manuscript verified the occurrence of differences in the correlations between performance in the creativity tests and the estimates made in the techniques that measure the metacognition for different performance groups: 25% of students with minors and 25% of the students with higher scores in the tests of creativity.
Metacognitive knowledge and monitoring in tasks that involve creativity
Keywords: Metacognição; Criatividade; Monitoramento metacognitivo; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA